1983
DOI: 10.1080/14640748308402142
|View full text |Cite
|
Sign up to set email alerts
|

Kinaesthesis: Its Measurement, Training and Relationship to Motor Control

Abstract: This paper reviews studies which demonstrate the importance of kinaesthesis in the acquisition and performance of motor skills. A method of measuring kinaesthetic sensitivity in children and adults (recently developed) is briefly described. Developmental trends in kinaesthetic perception are discussed and large individual differences found within age groups. It was shown that kinaesthetically undeveloped children can be trained to perceive and memorize kinaesthetic information with greatly improved accuracy. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1
4

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 17 publications
4
54
1
4
Order By: Relevance
“…Thus, it is difficult to tell if the different pattern of responding derives from something intrinsic to haptic coding or from minimal practice with T-like, twodimensional patterns. Practice has been shown to have a robust effect on kinesthetic judgments, as revealed by drawing (Laszlo & Bairstow, 1983). It is impossible, of course, to rule out the visual imagery interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is difficult to tell if the different pattern of responding derives from something intrinsic to haptic coding or from minimal practice with T-like, twodimensional patterns. Practice has been shown to have a robust effect on kinesthetic judgments, as revealed by drawing (Laszlo & Bairstow, 1983). It is impossible, of course, to rule out the visual imagery interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…A related finding is that the level of motor involvement of a task also affects performance. A meta-analysis of 50 studies on Developmental Coordination Disorder children by Wilson and McKenzie (1998) established that effect sizes were higher for studies that involved active movement (e.g., Hulme, Biggerstaff, Moran & McKinlay, 1982) than passive movement (e.g., Laszlo & Bairstow, 1983). Other studies have also demonstrated that an active condition of a motor test, rather than a passive one, significantly discriminates Developmental Coordination Disorder children from a control group (e.g,.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating kinesthetic training on drawing tasks in children aged 6 to 8 years (N = 24) found improvements in the treatment group, however no between-group comparisons were made with the control group (Laszlo & Bairstow, 1983). First grade children (N = 30) with handwriting difficulties had low grip scores and lower scores for kinesthesia on a drawing task when compared with children without handwriting difficulties (N = 30) (Schneck, 1991).…”
Section: Sensorimotor Perceptual and Cognitive Processes Involved Inmentioning
confidence: 99%
“…Kinesthetic feedback provides information about arm movement, and assists with monitoring errors and motor learning (Laszlo & Bairstow, 1983). A study investigating kinesthetic training on drawing tasks in children aged 6 to 8 years (N = 24) found improvements in the treatment group, however no between-group comparisons were made with the control group (Laszlo & Bairstow, 1983).…”
Section: Sensorimotor Perceptual and Cognitive Processes Involved Inmentioning
confidence: 99%